A Paradigm Shift from Emergency Response to Reconstruction and Rehabilitation: Creation of Peak National Body for Disaster Management in Pakistan - Khan, Shahed; Ashori, Fida Hussain (2015)
The earthquake of 8 October 2005, an unprecedented disaster in the history of Pakistan, led to an equally exceptional national response. Reconstruction and rehabilitation of affected areas was indeed a herculean task. The Earthquake Reconstruction and Rehabilitation Authority (ERRA) was immediately established as a peak national body with extraordinary powers and mandate to ensure coordinated actions for rescue, relief, reconstruction and rehabilitation. The national institutional set up was forced to readjust rapidly to convert this adversity into an opportunity to improve its capability to deal with disasters. This paper aims to provide an overview of the institutional strategy and measures undertaken in the wake of the 2005 earthquake. It looks at the strengths and weaknesses of installing an efficient entity largely adopting a command and control approach to efficiently and effectively deliver reconstruction projects on the ground. The paper seeks to derive lessons that can be useful for governments considering the setting up of comprehensive proactive disaster management systems.